PENGARUH KEPUTUSAN INVESTASI, PENDANAAN, KEBIJAKAN DIVIDEN DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Clementin, Felly Sintinia; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
One of the primary objectives of the company is to maximize the firm value. The firm value is theperception of investors to the company which is mostly related with the stock price. The stock price is formedfrom investorâs demand and supply of the companyâs shares, so the stock price may be used as a proxy for thefirm value. This research is meant to test the influence of investment decision, financing decision, dividendpolicy, and profitability to the firm value. The samples of this research are 35 manufacturing companies whichare listed in Indonesia Stock Exchange (IDX) in 2012-2014 periods are in accordance with the determinedcriteria. This research is conducted by using purposive sampling method. The data source of this research hasbeen retrieved from Indonesia Stock Exchange (IDX). The data analysis of this research is done by usingmultiple linear regressions analysis with the instrument of SPSS application (Statistical Product and ServiceSolutions). The result of this research shows that the investment decision has influence to the firm value,financing decision does not have any influence to the firm value, dividend policy has influence to the firm value,and profitability has influence to the firm value.Keywords: investment decision, financing decision, dividend policy, firm value.